Improving diet quality for female workers through market innovations: evidence from Assam’s tea estates - Das, Shantanu; Porwal, Akash; Sharma, Anshita; Wangila, Fred; Djimeu Wouabe, Eric; Fokou, Carrel; Choubey, Aishwarya; Woltering, Kris; Mmbuya, Mduduzi; Nyhus Dhillon, Christina (Frontiers in Nutrition, 2025)
IntroductionDespite the economic significance of the tea industry in India, its female workers suffer from high rates of malnutrition, particularly anemia. A three-year intervention aimed to improve diets among tea workers through behavior change and supply-side strategies across tea estates in Assam, India. Key activities included community-based edutainment, cooking demonstrations, and a market-based approach to increase access to nutritious foods via door-to-door entrepreneurs or local shops.MethodsThe study used a mixed method, repeated cross-sectional design. Baseline (Feb–Mar 2021) and endline (Mar–Apr 2023) data were collected via household surveys (989 tea workers, 66 clusters), 20 key informant interviews, and 10 focus group discussions. A multi-stage sampling design selected 30 estates, 66 divisions, and 15 households per division. Women aged 15–49 were the primary respondents. Monitoring data tracked coverage and outputs. Propensity score matching controlled for differences in selected households.ResultsThe estimated intervention effect was a 38.3 percent increase in the consumption of vitamin A-rich fruits and vegetables and a 13.2 percentage point increase in the consumption of fortified cooking oil. Overall, this resulted in a 28.2 percentage point increase in the proportion of women meeting a minimally diverse diet. Some differences were seen across the market-based models.ConclusionThe intervention’s combination of supply-side innovations and behavior change efforts was effective and highlighted the potential for market-based approach to positively transform food environments in low-income settings. Future research should explore the long-term sustainability of such market-based interventions in improving nutritious foods consumption.